The Employment of Real-Time Polymerase Chain Reaction Using Species-Specific Primer Targeting on D-Loop Mitochondria for Identification of Porcine Gelatin in Soft Candy - Sudibyo Martono; Abdul Rohman; Nina Salamah; Yuny Erwanto (Indonesian Journal of Chemistry, 2021)
Analysis of non-halal components, such as pork and porcine gelatin, in food and pharmaceutical products is a need for halal authentication study. This research was aimed to develop a species-specific primer (SSP) to analyze DNA in porcine gelatin in soft candy using real-time PCR. The SSP to porcine DNA primer is designed using NCBI and Primer-BLAST software. The designed primer was subjected to a validation by assessing some parameters, including specificity, sensitivity, repeatability test, and linearity. The results showed that the real-time PCR with SSP targeting on mitochondrial D-loop specifically able to identify the presence of porcine DNA at an optimum annealing temperature of 50.5 °C. The coefficient of variation (CV) on repeatability analysis of Cq was 0.53%, and the efficiency value (E) for DNA amplification was 100%. Real-time PCR using D-LOOP porcine primer (forward: ACTTCATGGAACTCATGATCCG; reverse ATGTACGTTATGTCCCGTAACC) can also be successfully used for the identification of porcine gelatin DNA in soft candy.